A cascade double 1,4-addition/intramolecular annulation strategy for expeditious assembly of unsymmetrical dibenzofurans - Xinwei He (Nature Portfolio, 2021)
Existing routes to dibenzofurans have intrinsic regioselectivity, limiting the substitution patterns available in the products. Here a double 1,4-conjugate addition-annulation cascade between propargylamines and imidazolium methylides provides direct access to dibenzofurans with a complementary substitution pattern.